Fostering EFL learners’ motivation, anxiety, and self-efficacy through computer-assisted language learning- and mobile-assisted language learning-based instructions - Dong, Li; Jamal Mohammed, Shireen; Ahmed Abdel-Al Ibrahim, Khaled; Rezai, Afsheen (Frontiers in psychology, 2022)
In the literature, a mass of studies have inspected the effects of computer-assisted language learning (CALL) and mobile-assisted language learning (MALL) on Iranian English as a Foreign Language (EFL) learners’ achievement. However, the effects of CALL and MALL on psychological factors, such as motivation, anxiety, and self-efficacy, have largely remained unexplored. Thus, this study explored the effects of CALL and MALL, and face-to-face (FTF) learning environments on Iranian EFL learners’ motivation, anxiety, and self-efficacy. To this aim, using a random sampling method, a total of 137 male EFL intermediate learners were selected and homogenized using the Oxford Quick Placement Test (OQPT). Based on the test scores, a total of 90 EFL learners were selected and randomly assigned to three groups, namely, CALL ( n = 30), MALL ( n = 30), and FTF ( n = 30). Then, the participants’ motivation, anxiety, and self-efficacy were gauged prior to the instructions. Afterward, they received CALL-based, MALL-based, and conventional instructions which lasted 25 1-h sessions held twice a week. At the end of the instructions, the participants’ motivation, anxiety, and self-efficacy were measured again. The collected data were analyzed through a one-way MANOVA. Findings evidenced that the experimental groups’ motivation, anxiety, and self-efficacy were positively affected by the CALL-based and MALL-based instructions. However, there was not a statistically significant difference between the CALL group and MALL group concerning the gains of motivation, anxiety, and self-efficacy. In light of the findings, a range of implications is suggested for relevant stakeholders.